Pengembangan Literasi Anak Melalui Permainan Dadu Literasi Di TK AL-AQSHO Konawe Selatan (PIAUD IAIN Kudus, 2020)
Abstract: DEVELOPMENT OF CHILDREN LITERATION THROUGH LITERATING DADU GAMES IN TK AL-AQSHO KONAWE SELATAN. Literacy is an aspect of language development in early childhood education. Literacy is often associated with the words reading and writing, although the terminology of literacy is broader than reading and writing. The aim of this article is to describe the development of children's literacy through the literacy dice game. The researcher used a qualitative approach with a descriptive analysis method, with the subject of the study being the children of group A TK Al-Aqsa South Konawe determined by the researcher by purposive sampling. Techniques of data analysis using an interactive model with the steps of data reduction, data presentation, conclusions drawn and verification. The results showed that children's literacy on child development indicators can recognize symbols for reading preparation, children can recognize the initial letters of the names of objects, write and pronounce letters a-z and children can write their own names. All indicators of children's literacy develop very well through the use of literacy dice games.Keywords: Literacy, Children, Games Abstrak: Literasi merupakan aspek perkembangan bahasa dalam pendidikan anak usia dini. Literasi sering dilekatkan pada istilah membaca dan menulis, walaupun terminologi literasi lebih luas dari baca-tulis. Tujuan penulisan artikel ini untuk mendeskripsikan pengembangan literasi anak melalui permainan dadu literasi. Peneliti menggunakan pendekatan kualitatif dengan metode analisis deskriptif, dengan subjek penelitian yaitu anak kelompok A TK Al-Aqsho Konawe Selatan yang ditetapkan peneliti secara purposive sampling. Teknik analisis data menggunakan interaktif model dengan langkah-langkah yaitu reduksi data, penyajian data, penarikan kesimpulan dan verifikasi. Hasil penelitian menunjukkan bahwa literasi anak pada indikator perkembangan anak dapat mengenal simbol untuk persiapan membaca, anak dapat mengenal huruf awal dari nama benda, menuliskan dan mengucapkan huruf a-z dan anak dapat menuliskan nama sendiri. Seluruh indikator literasi anak tersebut berkembang dengan sangat baik melalui penggunaan permainan dadu literasi.Kata kunci: Literasi, Anak, Permainan